Nationalization and Naturalization of the Universal Science -The Case of the 1830 Debate between Cuvier and Saint-Hilaire- - 김서현 (서양사론, 2024)
Through the case study of the scientific debate between Georges Cuvier and Étienne Geoffroy Saint-Hilaire at the French Academy of Sciences in 1830, this article traces the dual process of nationalization and naturalization of scientific thoughts. Even though both Cuvier and Saint-Hilaire were French, nationalistic discourses permeated the debate as one criticized the other as practicing the “German science” and each promoted his own practice as the true “French science.” I argue that it was the methodological difference, especially the different types of vision and chronoception, that allowed the concept of nationality to serve as one of the identifiers for the contending scientific thoughts. Then I examine the texts in and around the debate to identify the instances of interaction between nation and science: nationalization of scientific ideas and achievements, naturalization of nationalized sciences, as well as scientization of nationalities. Through this examination, I argue that both Cuvier and Saint-Hilaire, and their followers (including Goethe) of diverse disciplines and nationalities, interpreted the debate in terms of national differences in one way or another. The conflict between, and merging of, the taxonomic impulse and evolutionary understanding of nature, the concepts of unity and diversity, natural science and nationalism, reflected not just the development of biological science at that time, but also the general confusion about how to interpret and manage the post-Revolutionary world that seemed to constantly change without an anchor. I conclude that the very topics of 19th-century natural science came to penetrate the sociological practice of science, all the while naturalists chased the ideal of the “universal science.”
Keywords: 19세기 프랑스; 민족주의; 자연과학; 조르주 퀴비에; 에티엔 조프루아 생틸레르; 19th-century France; Nationalism; Natural science; Georges Cuvier; Étienne Geoffroy Saint-Hilaire